Quality Evaluation of Voice Transmission Using BPL Communication System in MV Mine Cable Network - Debita, Grzegorz; Falkowski-Gilski, Przemyslaw; Habrych, Marcin; Miedzinski, Bogdan; Wandzio, Janusz; Jedlikowski, Przemyslaw (Elektronika ir Elektrotechnika, 2019)
This article presents results of a quality evaluation study, considering voice transmission in a 6 kV medium voltage cable network using the BPL (Broadband over Power Line) communication system. The tests are carried out under real mining conditions for the selected power cable without voltage, earthed at both sides. Such a method of monitoring work conditions is of great importance, especially during a disaster. Power cables are potentially resistant to mechanical damage and, thus, ensure continuity of transmission, also, in cases of electricity stoppage and partial damage (interruption) of the phase conductors. The voice transmission quality is tested for a relatively low bitrate of 8 kbps–48 kbps using both induction and mixed induction-capacitive coupling with the power cable. Such a solution should provide both reliable and high-quality services, considering clear and understandable voice messages to people. The quality evaluation is carried out on a group of 15 people aged between 25–35 years old. The tested signal samples consist of voice messages in British English, German, and Polish. On the basis of the investigated results, respective conclusions are formulated.